Tensions identitaires d’enseignants d’éducation socio-culturelle au sein d’une transition sociétale et agroécologique - Séverine Bon; Nathalie Panissal (Éducation et Socialisation)
We investigate some issues of teachers confronted to the education of the so-called agro-ecological transition, which has been recently introduced in official curriculum. With a comprehensive, exploratory and qualitative approach, we use semi-directed interviews of four teachers in cultural education inside an agricultural high school. We analyse specifically the problems of their identities (professional tension) and their involvement in this new educational program through four criteria: intentionality, temporality and sociality. The results of our analysis show that these teachers, while being questioned by this new educational challenge, still continue to use pre-existing educational practices and are poorly engaged in the project.